Review on performance aspects of Nearly Zero-Energy Districts - Amaral, Ana Rita (2018)
The nearly zero-energy concept aims to achieve a significant reduction of energy consumption in the buildings’ sector, while promoting the renewable energy dissemination. In order to move beyond the individual building boundary and to consider the urban context influence, this article presents a critical review on the aspects of applying the nearly zero-energy principle to the intermediate urban scale known as district, from an architectural and urban planning perspective. A contextualization on the definition of district is proposed, as well as a delimitation of the various urban scales and respective levels of detail, regarding the establishment of the Nearly Zero-Energy District (NZED) concept. Key urban elements as morphology, climate and public spaces are identified in literature, namely the geometric indicators that potentially influence districts’ performance. The developed methodologies for calculating districts’ energy performance and the respective metrics are explored as well. At the aftermath, challenges for further research opportunities are discussed, namely the need to develop methods to evaluate the real impact of the reviewed urban elements, to appraise the interrelations between climatic and morphological indicators, and especially to accurately include them in the energy performance assessment methodologies of districts.